A Study of the Corrosion Behavior of AHSS Complex-Phase CP 780 Employing an Electrochemical Noise Technique Analyzed by Different Methods - Lara Banda, María del Refugio; Almeraya Calderón, Facundo; Jáquez Muñoz, Jesús Manuel; Nieves Mendoza, Demetrio; Baltazar Zamora, Miguel Ángel; Olguín Coca, Javier; Estupiñan López, Francisco Humberto; Cabral Miramontes, José Ángel; Santiago Hurtado, Griselda; Gaona Tiburcio, Citlalli (Molecular Diversity Preservation International, 2025)
The automotive industry employs structural steels with E-coats to reduce weight and increase the corrosion resistance of chassis, reducing CO2 emissions. Due to their mechanical properties, part of the chassis is a composite of advanced high-strength steels (AHSS). AHSSs are coated by conversion methods such as phosphate to increase epoxy coating adherence and corrosion resistance. The main point of this research is to characterize an AHSS complex-phase (CP) 780 in blank, with a phosphate coating and an E-coat organic coating using electrochemical noise, employing time-domain, frequency-domain, time–frequency-domain, and chaotic system methods to determine the type and corrosion kinetics of each system. The electrochemical noise technique was made with a conventional three-electrode cell, using a saturated calomel as a reference electrode. Data were recorded at 1024 s, at 1 data per second in a 3.5 wt. % NaCl electrolyte, according to ASTM G199-09. The results show how AHSS CP 780 presented uniform corrosion, similarly to the phosphate sample; however, the E-coat presented a trend of a localized process when analyzed by Wavelets transform. On the other hand, corrosion resistance increased for the E-coat sample, with values of 2.58 × 106 Ω·cm2. According to the results of the research, all the samples are susceptible to present localized corrosion.